Comparing routine versus selective use of intraoperative cerebral angiography in aneurysm surgery: a prospective study. (25th November 2014) - Washington, Chad W; Derdeyn, Colin P; Chicoine, Michael R; Cross, DeWitte T; Dacey, Ralph G; Moran, Christopher J; Rich, Keith M; Zipfel, Gregory J
Abstract : Introduction: While the use of intraoperative angiography (IA) has been shown to be a useful adjunct in aneurysm surgery, its routine use remains controversial. Objective: We wished to determine if IA is required in all patients undergoing aneurysm surgery (ie, routine IA) or if intraoperative assessment can reliably predict the need for IA (ie, select IA). Methods: We prospectively evaluated all patients undergoing craniotomy for aneurysm clipping. In these patients, the treating surgeons were asked to record whether they felt IA was required at two time points: (1) prior to surgery and (2) immediately after clip application but before IA. All patients underwent IA as per the institutional protocol. IA results and the need for post-IA clip adjustments were recorded. Results: Of the 200 patients enrolled, 197 were included for analysis. IA was deemed necessary on preoperative assessment in 144 cases (73%) and on post-clip assessment in 116 cases (59%). Post-clip IA demonstrated 47 (24%) positive findings and post-IA clip adjustments were made in 19 of 198 cases (10%). On preoperative assessment, there were four cases where IA was deemed unnecessary, yet post-IA clip adjustment was required, resulting in a sensitivity of 79% and false negative rate of 8%. Regarding post-clip assessment, there were five cases where IA was thought to be unnecessary and clip adjustment was required, resulting in a sensitivity of 73% and false negative rate of 6%. Conclusions: The accuracy of a strategy of select IA was not improved by assessing the need for IA immediately after aneurysm clipping versus prior to surgery onset. This suggests that intraoperative assessment regarding the adequacy of aneurysm clip application should be viewed with caution.